Case study: inter-floor leakage in high-rise residential buildings in Malaysia - Siti Rosemawar Mohd Sahi,; Norngainy Mohd Tawil,; Nurfidatul Ema Saaidin,; Kuan, You Wai (Penerbit Universiti Kebangsaan Malaysia, 2023)
Building defects are a common issue in the construction industry. Defects of high-rise buildings, such as cracks and leaks, are often caused by poor workmanship, and insufficient and low-quality building materials. Other contributing factors to building defects are inadequate cooperation during construction, poor design and improper installation. Inter-floor leakage is a widespread matter in new homes, leaks are detected late and repeated leaks occur even after repairs have been carried out. Inter-floor leakage often occurs in new homes. Leaks are detected late and repeated ones occur even after repairs are carried out. This study aims to diagnose buildings with inter-floor leakage problems by using several diagnostic tools and techniques like visual, destructive and nondestructive tests. Experts use testing equipment to determine moisture and appropriate maintenance or repair. A case study is carried out on a residential unit with a leak in the ceiling due to a crack on the rooftop. The findings of the study can provide knowledge about building diagnosis to property owners and property managers, identifying the cause of leaks and enabling early detection of building defects and suggested repairs to prevent similar leaks from occurring. By utilizing diagnostic tools and techniques, owners and property managers can detect problems early, minimizing damage and expenses in the long run. Based on the study, existing cracks can be converted into expansion joints, white paint can be used on the walls to control heat, installed thermal insulation to control solar energy stress and waterproof membrane can be applied to prevent moisture penetration.